2009
DOI: 10.1007/s11240-009-9639-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sucrose and pH levels on in vitro shoot regeneration from leaf explants of Bacopa monnieri and accumulation of bacoside A in regenerated shoots

Abstract: Brahmi (Bacopa monnieri) is an important medicinal plant mainly used for the treatment of neurological disorders and depression. Recent investigations revealed that bacoside A is major chemical component shown to be responsible for memory facilitating action of brahmi. The current investigation was carried out to assess the potential for increasing biomass and the concentration of bacoside A in the in vitro regenerated shoots by varying sucrose and pH levels of shoot regeneration medium. The leaf explants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 15 publications
6
30
0
3
Order By: Relevance
“…Similar findings were reported by Siddique and Anis (2007a) in Cassia angustifolia and B. monnieri (Naik et al 2010) and Perveen et al (2011) in Albizia lebbeck. These studies indicated that the effect of pH value on plant regeneration depends on plant species.…”
Section: Medium Ph Levelssupporting
confidence: 87%
“…Similar findings were reported by Siddique and Anis (2007a) in Cassia angustifolia and B. monnieri (Naik et al 2010) and Perveen et al (2011) in Albizia lebbeck. These studies indicated that the effect of pH value on plant regeneration depends on plant species.…”
Section: Medium Ph Levelssupporting
confidence: 87%
“…The effects of different PGR, medium strength and pH value on secondary metabolite accumulation have previously been studied in various plants [11,12,13] though limited data exist on the topic regarding S. rebaudiana [7,14]. In the present study, half-rather than fullstrength Murashige and Skoog (MS) media was used for the experiments as our preliminary data showed far better germination, growth and development of plantlets in lower salt media.…”
mentioning
confidence: 93%
“…The pH also influences the status of the solidifying agent in medium, a pH higher than 6 produces a very hard medium and a pH lower than 5 does not sufficiently hard medium (Bhatia and Ashwath, 2005). The reduced pH might favor the assimilation of ions by the cultured cells from the medium and in turn regulation of metabolic pathway of cultured cells (Naik et al, 2010). From above studies, it can be concluded that MS basal media at pH was found most optimum for shoot proliferation in papaya.…”
Section: Resultsmentioning
confidence: 86%